The Cultural Dimension of Clinical Vulnerability: Repeated Access to Emergency Units and Discontinuity in Health and Social Care Pathway - Laura Bertini-Soldà (Societies, 2023)
Swiss health and social care system is complex and is based on universal coverage. However, discontinuity in health and social path and repeated access to emergency units are symptoms of inequity. The aim of this paper is to highlight the interactions between vulnerable patients with socio-sanitary actors to propose some innovative solutions to promote social justice. A six-month ethnography of 15 vulnerable patients’ health and social transitions in the region of Ticino Canton in Switzerland gives new insight into conflict situations in assistance relationships, where reciprocal stereotyping between professionals and patients undermines continuity of care. The cultural dimension of health and social institutions is identified in the problem-solving approach which is legitimized as the only one for dealing with complex situations. The analysis shows how clinical vulnerability relates strongly to an unmanaged so-called liminality phase. Culture is an invisible dimension in care, but its effects on equity are major. Two possible interventions are discussed, which are culturally informed reorganization of the care network and collaboration with a sociosanitary cultural mediator.